The Role of TikTok User-Generated Content (UGC) and Electronic Word of Mouth (e-WOM) in Shaping Cafe Visit Intentions among Gen Z - Latifa, Baiq Isnina; Indriani, Sri; Meisaroh, Firda (Transpublika Publisher, 2026)
The rapid growth of short video-based social media, particularly TikTok, has reshaped information-seeking behavior and decision-making among Generation Z, including their intentions to visit cafes. As digital natives, Generation Z tends to rely on visual, authentic, and experience-based content shared by other users. The purpose of this research is to analyze how User-Generated Content (UGC) and Electronic Word of Mouth (e-WOM) influence the intention of Generation Z students in Malang City to visit cafes. A quantitative explanatory method was utilized for this study. The target group consisted of active Generation Z students in Malang City who are users of TikTok. A sample of 150 participants was chosen through purposive sampling. Information was gathered through online surveys utilizing a four-point Likert scale. The variables studied were UGC (X₁), e-WOM (X₂), and visit intention (Y). Employing multiple linear regression in IBM SPSS, the analysis shows a positive and significant link between UGC and students’ intention to visit cafes in Malang City. A comparable positive and significant relationship was found for e‑WOM. Simultaneously, UGC and e-WOM significantly affect visit intention, demonstrating that authentic user content combined with digital social interaction on TikTok effectively builds trust, positive perceptions, and interest in visiting cafes. UGC and e-WOM on TikTok play a strategic role in shaping Generation Z’s intention to visit cafes. Café operators are encouraged to stimulate authentic user content creation and manage digital interactions and reviews effectively on TikTok. Future studies are recommended to incorporate additional variables and expand research settings.